Solid Waste Generation and Characterization in Ilorin, Nigeria - Mokuolu, O. A.; Iji, J. O.; Aremu, S. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Global per capita waste generation rates and characterization vary by regions, countries, and within cities. The generation, l and characterization of waste from selected areas in Ilorin, Nigeria, prone to indiscriminate disposal of solid waste without consequence were analyzed for proper management. Municipal solid wastes were sorted, analyzed by weight and percentage composition using the quantitative approach. The average generated waste per capita was estimated to be 0.66 kg/day, w/w distribution was 57.53% food waste, 9.07% nylon (flexible films), 5.98% plastic (rigid containers),4.95% textile, 10.51% paper and 11.96% others. The average moisture content was 46.16% food waste, 20.63% nylon, 18.65% plastic, 36.67% textile, 18.45% paper and 42.89% others. The results show an average bulk density of 10.36 Kg/m3 of food waste, 2.14 of nylon, 0.5 of plastic; 0.93 of textile; 2.74 of paper and others 5.36. The chemical analysis showed that volatile matter ranged from 20.55 to 24.10%, ash content 3.10to 3.90%, fixed carbon 7.5to 9.8%, calorific value 14820to 18360 (kJ/kg), nitrogen 0.40to 0.50%, hydrogen 4.38to 5.80%, carbon 40.90 to 44.30%, oxygen 30.80 to 34.60%, Sulphur 0.19 to 0.24%, fusing point of ash 3.12to 4.38 °C, and heating value from 13.520to 13.64 KJ/Kg. The results generated could play a positive role in the management of solid waste in that area.